An Integrated Insight into the Relationship between Soil Microbial Community and Tobacco Bacterial Wilt Disease - Yang, Hongwu; Li, Juan; Xiao, Yunhua; Gu, Yabing; Liu, Hongwei; Liang, Yili; Liu, Xueduan; Hu, Jin; Meng, Delong; Yin, Huaqun (Frontiers in Microbiology, 2017)
The soil microbial communities play an important role in plant health, however, the relationship between the below-ground microbiome and above-ground plant health remains unclear. To reveal such a relationship, we analyzed soil microbial communities through sequencing of 16S rRNA gene amplicons from 15 different tobacco fields with different levels of wilt disease in the central south part of China. We found that plant health was related to the soil microbial diversity as plants may benefit from the diverse microbial communities. Also, those 15 fields were grouped into ‘healthy’ and ‘infected’ samples based upon soil microbial community composition analyses such as unweighted paired-group method with arithmetic means (UPGMA) and principle component analysis (PCA), and furthermore, molecular ecological network analysis indicated that some potential plant-beneficial microbial groups, e.g. Bacillus and Actinobacteria could act as network key taxa, thus reducing the chance of plant soil-borne pathogen invasion. In addition, we propose that a more complex soil ecology network may help suppress tobacco wilt, which was also consistent with highly diversity and composition with plant-beneficial microbial groups. This study provides new insights into our understanding the relationship between the soil microbiome and plant health.